Sistem Informasi Geografis Pemetaan Dan Analisis Kebutuhan Serta Prefensi Pelanggan Terhadap Layanan Penjahit Berbasis Web Di Kota Baturaja - Aditiya Syahputra; Salman Al Farisi; Pujianto Pujianto; Destiarini Destiarini (UNIVED Press, 2025)
This study aims to analyze customer needs and preferences for web-based tailoring services in Baturaja City. Abstract-This study aims to analyze customer needs and preferences for web-based tailoring services in Baturaja City. This research adopts quantitative and qualitative approaches with data collection conducted through in-depth interviews with potential customers. The results showed that the majority of customers need tailoring services that can be accessed online, have online ordering features, cost estimation, and estimated processing time. Key customer preferences include ease of site navigation, price transparency, and speed of service response. This study provides recommendations for the development of a digital platform that can improve customer satisfaction while expanding the market reach for local tailors in Baturaja.